PELATIHAN DIGITAL ASSESSMENT BERBASIS ANDROID DI SMA NEGERI 1 PANGKEP - Sri Maya; HIkmah Rusdi; Warda Murti (PPM LP2M UIN Alauddin Makassar, 2022)
This PKM activity aims to share information with educators regarding Digital Assessment learning which can be accessed via Android. The target of this activity is SMAN 1 PANGKEP Teachers. The method used in this PKM activity is in the form of: 1) area observation to observe the situation and condition of the school 2) coordination carried out with the vice principal of student affairs 3) socialization of activities to provide information related to program plans to the school community, especially the teachers of SMAN 1 PANGKEP 4) implementation activities in the form of Android-based Digital assessment training seminars. This activity was attended by 29 participants consisting of lecturers, teachers and students. The activity took place with the enthusiasm of the participants in receiving the material which was shown by the active participation of the participants in the activity.